2018
DOI: 10.1002/chem.201801972
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Deoxygenation and Reductive Disilylation of Nitroarenes by Organosilicon Reducing Reagents

Abstract: A metal-free deoxygenation and reductive disilylation of nitroarenes was achieved using N,N'-bis(trimethylsilyl)-4,4'-bipyridinylidene (1) under mild and neutral reaction conditions, and a broad functional group tolerance was possible in this reaction. Mono-deoxygenation, giving a synthetically valuable N,O-bis(trimethylsilyl)phenylhydroxylamine (7 a) as a readily available and safe phenylnitrene source from nitrobenzene, and double-deoxygenation, giving N,N-bis(trimethylsilyl)anilines 8, were easily controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Silanes and disilanes has long been known to promote the reduction of nitroarenes even in the absence of a metal catalyst and the reaction can be employed for the synthesis of heterocyclic compounds, [215][216][217] but high temperatures are needed unless activated silanes are employed. [217] Iron complexes have been found to catalyze the reduction of nitroarenes to anilines by phenylsilane. [218] A single example of the use of a copper catalyst in the reductive cyclization of a nitrostyrene to indole by a silane was reported in 2011 by Taylor and Correia (Scheme 87).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Silanes and disilanes has long been known to promote the reduction of nitroarenes even in the absence of a metal catalyst and the reaction can be employed for the synthesis of heterocyclic compounds, [215][216][217] but high temperatures are needed unless activated silanes are employed. [217] Iron complexes have been found to catalyze the reduction of nitroarenes to anilines by phenylsilane. [218] A single example of the use of a copper catalyst in the reductive cyclization of a nitrostyrene to indole by a silane was reported in 2011 by Taylor and Correia (Scheme 87).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Moreover, in the last decades, the focus on green and sustainable methodologies, also associated to the progress of organocatalysis, [7] stimulated the study of metal-free processes. In this context, a great variety of non-metal and transition metal free reagents were exploited for the reduction of nitro aromatics to anilines such as 9,10-dihydroanthracene, [8] 1,4-dihydropyridine systems, [9] elemental sulfur, [10] thiols, [11] Baker's Yeast in basic solution, [12] fullerene/H 2 , [13] glucose, [14] vasicine, [15] trichlorosilane/NR 3 , [16] triethylsilane/B(C 6 F 5 ) 3 , [17] diboron compounds, [18] viologen/Na 2 S 2 O 4 , [19] N,N'-bis(trimethylsilyl)-4,4'bipyridinylidene, [20] 2-aminoquinazolin-4(3H)-one/N 2 H 4 , [21] char-coal/NaBH 4 in aqueous medium, [22] as well as different carbonbased catalysts in the presence of N 2 H 4 , [23] NaBH 4 , [24] isopropanol, [25] or subcritical water [26] as hydrogen sources, and even the system isopropanol/KOH. [27] Recent studies from our laboratory showed the possibility to apply pyridylmethanols as hydrogen donors, mimetic of Hantzsch ester (HEH), for metal free reductions of aromatic/ heteroaromatic nitro compounds to the corresponding amines.…”
Section: Introductionmentioning
confidence: 99%
“…While it was originally envisioned that elimination of (Me 3 Si) 2 O from MO n by 1 might be a useful approach to MO n −1 , a recent application to support‐bound WO 3 gave instead tetravalent tungsten silyl esters, which is still a valuable 2 electron reduction, but without full elimination of W/O bonds and creation of lower metal coordination number . The method has also been applied to nanoparticle formation, silylation of B−F bonds and of α‐halo carbonyls, and deoxygenation of nitro compounds . In summary, the strengths and limitations of this attractive reagent are only just emerging …”
Section: Introductionmentioning
confidence: 99%
“…[5c] The method has also been applied to nanoparticle formation, [5g] silylation of BÀFb onds [6] and of a-halo carbonyls, [7] and deoxygenation of nitro compounds. [8] In summary,t he strengths and limitations of this attractive reagent are only just emerging. [5c, 9] Finally,t he combination of Me 3 SiCl and KC 8 has become a popularw ay to functionalize reduced N 2 in metal complexes [10] and is speculated to involve Me 3 Si radicals; [1a, 11] the parasitic production of (SiMe 3 ) 2 is ap roblem with this reagentc ombination, and this might be improved using the bis-silyl transfer reagents 1 or 2.…”
Section: Introductionmentioning
confidence: 99%